2013
DOI: 10.1088/0004-637x/775/2/101
|View full text |Cite
|
Sign up to set email alerts
|

THE VELA PULSAR AND ITS LIKELY COUNTER-JET IN THEKsBAND

Abstract: We report the first high spatial resolution near-infrared imaging of the Vela pulsar in the K s band obtained with the new adaptive optics system recently mounted on the Gemini-South telescope. For the first time, we have firmly detected the pulsar in this band with K s ≈ 21. m 8, and have resolved in detail an extended feature barely detected previously in the immediate vicinity of the pulsar in the J s H bands. The pulsar K s flux is fully consistent with the extension of the flat optical spectrum of the pul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Our ALMA observations, together with archival VLT ones in the near-IR, also confirmed the existence of an extended emission structure (the "nebula") at 1. ′′ 4 from the pulsar (Zyuzin et al 2013). JWST observations would better characterise its spectrum in the near-IR/submm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ALMA observations, together with archival VLT ones in the near-IR, also confirmed the existence of an extended emission structure (the "nebula") at 1. ′′ 4 from the pulsar (Zyuzin et al 2013). JWST observations would better characterise its spectrum in the near-IR/submm.…”
Section: Discussionmentioning
confidence: 99%
“…The open triangles with the error bars are our ALMA data (see Table 1). The rest of the spectrum is built from measurements collected from the literature (see Danilenko et al 2011;Zyuzin et al 2013 and references therein). The dot-dashed line is the extrapolation of the near-UV-optical-near-IR PL spectrum (Zyuzin et al 2013) towards the ALMA bands.…”
Section: Discussionmentioning
confidence: 99%
“…The observed K s magnitudes and A V values for all pulsars except of J1357 and Vela are taken from Zharikov et al (2013). The observed K s magnitude for Vela is taken from Zyuzin et al (2013). X-ray data and other parameters of pulsars are adopted from Kargaltsev & Pavlov (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Zyuzin et al (2013) recently reported the extended feature seen in the NIR (K s band) which could be associated with bar at the base of the SE jet or could be analog of the Crab's inner knot. However, this result still requires confirmation.…”
Section: The Crab and Vela Pwne: Similarities And Differencesmentioning
confidence: 99%